Strengthening the resilience of the Moroccan labour market in the face of crises: towards the design of appropriate structural transformations. - Rachid Elkachradi; AitBouziane Rim (African Scientific Journal, 2023)
Over the past decade, the Moroccan labour market has seen many positive developments according to the World Bank's Morocco's Jobs Landscape report. However, there are some structural problems that deeply hamper the inclusion and dynamics of the labour market in Morocco, namely the slowdown in job creation and the shortage of jobs in the industrial sector. In this respect, Morocco has put in place important economic and legal measures to design a dynamic and inclusive labour market, in order to respond to societal challenges such as the fight against poverty and precariousness, the regularisation of informal economic activities, and the protection of women and youth against social discrimination. Despite the efforts to make the Moroccan market more dynamic and resilient, several structural dysfunctions persist, negatively impacting the pace of change. At this stage, the recurrent crises of recent years, notably the covid pandemic19, have shown the great fragility of the Moroccan labour market, which calls into question all the reforms adopted by Moroccan decision-makers to strengthen the resilience of this market. Restructuring the Moroccan labour market is an urgent, necessary and complex process that requires the coordination of several stakeholders, including governments, businesses and workers.